Microbiota-Related Changes in Unconjugated Fecal Bile Acids Are Associated With Naturally Occurring, Insulin-Dependent Diabetes Mellitus in Dogs - Jergens, Albert E.; Guard, Blake C.; Redfern, Alana; Rossi, Giacomo; Mochel, Jonathan P.; Pilla, Rachel; Chandra, Lawrance; Seo, Yeon-Jung; Steiner, Joerg M.; Lidbury, Jonathan; Allenspach, Karin; Suchodolski, Jan (Frontiers in Veterinary Science, 2019)
Changes in the gut microbiota have been linked to human metabolic diseases, including diabetes mellitus (DM). The bidirectional effects between intestinal microbiota and bile acids (BA) suggest that dysbiosis may be accompanied by altered BA homeostasis, thereby contributing to the metabolic dysregulation seen in DM. Dogs develop naturally-occurring DM which may also be associated with dysbiosis and altered BA metabolism. The study objective was to examine BA metabolism in dogs with naturally-occurring DM and to relate these findings with changes in their intestinal microbiota. A prospective observational study of adult dogs with a clinical diagnosis of DM (n=10) and healthy controls (HC, n=10) was performed. The fecal microbiota were analyzed by 16S rRNA gene next-generation (Illumina) sequencing. Concentrations of fecal unconjugated BA (fUBA) were measured using gas chromatography and mass spectrometry. Analysis of bacterial communities showed no significant difference for any of the alpha-diversity measures between DM dogs versus HC. Principal coordinate analysis based on unweighted Unifrac distance metric did not reveal significant clustering between dog groups (ANOSIM Unweighted: R=0.084; p=0.114). However, linear discriminate analysis effects size (LEfSe) detected differentially abundant bacterial taxa (=0.01, LDA score >2.0) on various phylogenetic levels. While Enterobacteriaceae was overrepresented in dogs with DM, the proportions of Erysipelotrichia, Mogibacteriaceae, and Anaeroplasmataceae were increased in HC dogs. Dogs with DM had increased concentration of total primary fUBA compared to HC dogs (p=0.028). The concentrations of cholic acid and the cholic acid percentage of the total fUBA were increased (p=0.029 and p=0.036, respectively) in the feces of DM dogs relative to HC dogs. The levels of lithocholic acid (both absolute value and percentage of the total fUBA) were decreased (p=0.043 and p=0.01, respectively) in DM dogs versus HC dogs. These results indicate that both intestinal dysbiosis and altered fUBAs are present in dogs with naturally occurring DM. The patterns of microbial imbalance and impaired BA homeostasis bear strong similarity to Type 2 DM in humans. The dog may represent a novel large animal model for advancing translational medicine research efforts (e.g., the development of new therapeutics and devices trialed in veterinary patients) in DM.